Maternal Oxygen Administration during Labor: A Controversial Practice - Isabella Abati; Massimo Micaglio; Dario Giugni; Viola Seravalli; Giulia Vannucci; Mariarosaria Di Tommaso (MDPI AG, 2023)
Oxygen administration to the mother is commonly performed during labor, especially in the case of a non-reassuring fetal heart rate, aiming to increase oxygen diffusion through the placenta to fetal tissues. The benefits and potential risks are controversial, especially when the mother is not hypoxemic. Its impact on placental gas exchange and the fetal acid-base equilibrium is not fully understood and it probably affects the sensible placental oxygen equilibrium causing a time-dependent vasoconstriction of umbilical and placental vessels. Hyperoxia might also cause the generation of radical oxygen species, raising concerns for the developing fetal cells. Moreover, this practice affects the maternal cardiovascular system, causing alterations of the cardiac index, heart rate and vascular resistance, and unclear effects on uterine blood flow. In conclusion, there is no evidence that maternal oxygen administration can provide any benefit in the case of a non-reassuring fetal heart rate pattern, while possible collateral effects warn of its utilization. Oxygen administration during labor should be reserved for cases of maternal hypoxia.